Jual Beli Benda Wakaf Untuk Pembangunan Masjid Istiqlal di Desa Palengaan Daja Pamekasan - Suyudi, Mohammad; Hariyanto, Erie (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2018)
Abstract: Muslim jurists agree that selling waqf property is forbidden A case happened when concrete pillars of a waqf mosque was sold in a mosque called Istiqlal in Daja village. The pillars were initially planned to be installed during rebuilding of the mosque. The research discovered that this pillar originated from charity. These pillars were re-sold to collect more fund from community to continue the rebuilding. Majority of sunni schools of law (Shafii, Maliki and Hanbali) view that such transaction is forbidden because there is no valid reason for selling the pillar. In addition, the seller is not the rightful person to do so. Meanwhile, Hanafi jurists allow such practice as long as all requirements are met, especially the availability of replacement property as well as fulfilment of all terms and conditions of selling. Key words: Waqf, selling property, mosque